STRATEGI PENDIDIKAN KEWIRAUSAHAAN DALAM MEMBENTUK KARAKTER PENGUSAHA MUDA DAN PELAKU BISNIS KECIL - Puput Rifani; Fina Nikmatul Kamelia; Seviani Najiyah; Ferida Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Entrepreneurship education is an important effort to develop the character of young entrepreneurs who are creative, innovative, independent, and capable of facing business challenges. This article aims to examine entrepreneurship education strategies in shaping the character of young entrepreneurs and small business actors. The study employed a literature review method by analyzing various sources, including books, scientific journals, and previous research. The findings indicate that entrepreneurship education plays a significant role in fostering self-confidence, creativity, discipline, responsibility, risk-taking ability, and perseverance. Effective strategies include integrating entrepreneurship into learning activities, implementing project-based learning, conducting simple business practices, utilizing digital technology, and collaborating with entrepreneurs and small and medium enterprises (SMEs). Furthermore, entrepreneurship education positively contributes to increasing entrepreneurial interest, business management skills, and the economic independence of young people. Therefore, strengthening entrepreneurship education is essential to support the development of competent and competitive young entrepreneurs.